Isolation and Characterization of Biosurfactant-Producing Lactic Acid Bacteria from Sauerkraut - MOHD SATRIA, ANIS HUDA BINTI (Enhanced Knowledge in Sciences and Technology, 2022)
Sauerkraut is a conventional fermented foods that contains lots of health benefits. One of the microbes that determines the success of fermentation is lactic acid bacteria (LAB). The purpose of this study is isolate and determine biosurfactant producing LAB in sauerkraut, to characterize the potential biosurfactant properties and to evaluate the antimicrobial activity of biosurfactant-producing LAB from sauerkraut. The commercial sauerkraut to be used can be purchased from the local supermarket in Pagoh. The sauerkraut isolated bacteria will be examined based on the morphological features and gram types. The isolated bacteria will be examined using haemolytic activity to evaluate the ability of microorganism in producing biosurfactant. For the characterization of biosurfactant stability, three common techniques will be used including oil displacement technique, drop collapse test and emulsification index. The evaluation of antimicrobial activity will be determined using agar disk diffusion and agar well diffusion method towards Escherichia coli and Bacillus cereus bacteria.